Las tormentas - Busch, Miriam (Washington, D.C. : National Geographic, 2017)
Looks at all the big storms created by Mother Nature run amok--from lightning and thunder to monsoons, hurricanes, and tornadoes.
Keywords: Storms -- Juvenile literature; Spanish language materials -- Juvenile literature; Spanish language -- Reading materials; Spanish language materials